Political Polarization based on Religious Identities: Empirical Evidence from the 2017 Jakarta Gubernatorial - UBAID, AHMAD HASAN; SUBANDI, H.B HABIBI (Universitas Muhammadiyah Yogyakarta, 2017)
According to a research conducted by Anis Baswedan, Saiful Mujani and R. Will- iam Liddle, political Islam in Indonesia during the post Reformation had a mod- erate and pluralistic character. But this qualitative case study finds that a new phenomenon of polarization based on religious identities emerges among vot- ers in the elections. In this article we argue that the results of the second round of the 2017 Jakarta Gubernatorial Election provide strong evidence that sup- ports the idea of ideological polarization. We apply the root cause model presented by Veldhuis and Staun to understand how Islamic radicalization occurs in the Jakarta election. In line with the argument of Mainwaring and Torcal, we also argue that due to weak institutionalization, political parties did not play a dominant role in shaping the sharp ideological gap among voters. We found that polarization of identity based on religiosity occurred due to social dynamics that were manufactured by campaign strategies and staff, politicians, and religious leaders. Political marketing strategies in the event of elections have, in fact, blatantly exploited the issue of religion as a political weapon in elections. It has led to the resurgence of religious identity in entering the political debate. Hence growing intolerance and conflicts based on religious identities during elections may have provided initial evidence to support the idea that Indonesian democracy is pro- gressing towards illiberal democracy.Â